Influence of Harvesting Time on Phytochemical Content of Colored Brown and Parboiled Rice - Nattareeporn Rodnuch; Kiattisak Burum; Chorkaew Aninbon (Agrivita Journal of agricultural science (AJAS), 2025)
Colored rice receives more attention from consumers because of its high phytochemicals and antioxidant activity beneficial to health. The aims of this investigation were to quantify the important phytochemicals and antioxidant activity in three varieties of colored rice for production of parboiled rice and to determine the effects of harvest time on phytochemicals and antioxidant activity in parboiled rice. Three colored rice varieties were planted in a split plot design with four replications. Main-plot was three rice varieties and sub-plot consisted four harvesting dates including 15, 20, 25 and 30 days after anthesis (DAA). Sangyod had the highest total phenolic content (77.34 mg GAE/100g), and harvest at 15 DAA provided the highest phenolic content (63.53 and 109.47 mg GAE/100g in brown and parboiled rice). Riceberry had the highest anthocyanin (65.91 mg/g seed), and harvest at immature stages gave the highest anthocyanin content. Riceberry also had the highest GABA content and harvest at 15 DAA had the highest GABA content. Harvest at 15 DAA had the highest antioxidant activities. Parboiling increased total phenolic content in Riceberry and Tubtin Chumphae and it increased GABA content in all rice varieties, but it reduced anthocyanin content.
Keywords: GABA and Rice Research